Wonosobo Regulation No. 3 of 2014 on Regarding Regional Organization to Achieve Good Governance - Ahmad Faqih (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The problems examined in this study is how effective and efficient arrangement of the bureaucracy of encouraging good governance, whether Wonosobo Regency Regulation No. 3 of 2014 is able to create efficiency and effectiveness of governance in Wonosobo, What are the obstacles and the solution? The research is a qualitative study using sociological juridical approach. Data collection methods used were observation, interview, and documentation. Then analyzed by qualitative analysis methods in order to produce a complete understanding. From the results of this research study concluded that There are two causes of delays in the implementation of the Regulation No. 3 of 2014 on the WTO technical factorsinvolves the placement of a new position at the WTO and non-technical factorsrelated to